Are Chemicals a Useful Tool for Glass Eel Traceability? - Pedro Reis; Mafalda Fernandes; Luís Pereira; Carlos Antunes (Fishes)
According to European reports, the population of Anguilla anguilla has declined to unsafe biological limits in most areas and current fisheries are unsustainable. Indeed, the European eel has been listed as a critically endangered species since the 1970s and has been on the IUCN Red List of Threatened Species since 2010. Glass eel fisheries in Europe are very limited, but illegal catches and international parallel trade are major threats to eel stocks due to their high commercial value. The main hypothesis of this study is that glass eels from each estuary have unique chemical profiles according to the ecological quality of the habitat. These unique chemical fingerprints were assessed using Chemical Integrating Approaches (CIA) based on multi-element (macro, trace and ultra-trace metals), global metabolome and stable isotope analyses. Thus, CIA are intended to be an effective chemical “weapon” to (i) fingerprint wild glass eels; (ii) fingerprint captive glass eels; (iii) authenticate and trace glass eels; and (iv) combat the illegal trade in juvenile European eels. The results of this study showed that Zn and Ni can fingerprint the chemical profiles of wild and captive glass eels and their geographical origin. In the same vein, metabolomes such as Butyric acid 4-vinylphenyl ester, N-(3-carboxypropanoyl)-Met, 2-(4-Methylphenyl)acetamide, N-formyl-glutamic acid, 3-Hydroxy-2-(3-methylbutanoylamino)propanoic acid, 4-Dodecylbenzenesulfonic Acid, Arginine and Pyrazole and the stable isotope 15N show potential as a chemical tools for glass eel traceability.